2014
DOI: 10.1016/j.neuroimage.2014.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Sparse representation based biomarker selection for schizophrenia with integrated analysis of fMRI and SNPs

Abstract: Integrative analysis of multiple data types can take advantage of their complementary information and therefore may provide higher power to identify potential biomarkers that would be missed using individual data analysis. Due to different nature of diverse data modality, data integration is challenging. Here we address the data integration problem by developing a generalized sparse model (GSM) using weighting factors to integrate multi-modality data for biomarker selection. As an example, we applied the GSM m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 37 publications
(55 reference statements)
0
46
0
Order By: Relevance
“…Considering n  ≫  m , we employed a SRVS method, proposed by [10] to solve Eq. (2) and identify potential biomarkers (gene expressions/SNPs) associated with BP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering n  ≫  m , we employed a SRVS method, proposed by [10] to solve Eq. (2) and identify potential biomarkers (gene expressions/SNPs) associated with BP.…”
Section: Methodsmentioning
confidence: 99%
“…The SRVS method has been shown to be feasible in identifying schizophrenia candidate biomarkers, while integrating functional magnetic resonance imaging data and SNP data [10]. It has also been demonstrated that the use of multiple data types may provide higher power to identify potential biomarkers that would be missed by using independent data analysis [11].…”
Section: Introductionmentioning
confidence: 99%
“…After a series of quality controls, we selected 184 subjects, including 80 SZ cases (age: 34 ± 11, 20 females and 60 males) and 104 healthy controls (age:32 ± 11, 38 females and 66 males). After pre-processing, 27,508 DNA methylation sites, 41,s236 fMRI voxels and 722,177 SNP loci were obtained for the subsequent biomarker selections [22,23,24,25,26,27].…”
Section: Data Preparationmentioning
confidence: 99%
“…Another important kind of feature selection methods for high dimensional data analysis is stability selection [44], [45], [46], which is based on resamplings (bootstrapping would behave similarly) and aims to alleviate the disadvantage of the plain ℓ 1 model, which either selected by chance non-informative regions, or neglected relevant regions that provide duplicate or redundant classification information [47], [48], [8], [49], [50], [51], [52]. One main advantages of stability selection is the finite sample control of false positives.…”
Section: Existing Extensions Of the Plain Sparse Modelmentioning
confidence: 99%
“…Recently, stability selection [44] based on the plain ℓ 1 model has been widely applied [50], [51], [52], due to its finite sample control of the false positives. In addition, it makes the choice of the regularization parameter insensitive.…”
Section: B Review Of Randomized Structural Sparsitymentioning
confidence: 99%